The influence of acelysin and nimotop on the cellular response of the hippocampus during the dynamics of experimental subarachnoid hemorrhage - Polkovnikov, O. Yu.; Tertyshnyi, S. I.; Полковніков, Олексій Юрійович; Тертишний, Сергій Ігорович (Запорізький державний медико-фармацевтичний університет, 2023)
Aim. Immunohistochemical study of rat hippocampal neurons and astrocytes at different time-points of experimental brain hemorrhage treated with acelysin and nimotop. Materials and methods. Subarachnoid hemorrhage (SAH) was modeled according to R. V. Dudhani et al. using 35 Wistar rats which were divided into 7 groups. Animals of the 1st and 2nd groups, for 4 and 7 days respectively received acelysin at a dose of 15 mg/kg once a day; animals of the 3rd and 4th groups received nimodipine at a dose of 0.3 mg/kg every 8 hours for 4 and 7 days. In groups 5th and 6th (control), SAH was modeled without treatment with observation periods of 4 and 7 days, respectively. The 7th group consisted of intact animals. Hippocampal CA1 fields were studied immunohistochemically evaluating the expression of CASP3, NeuN, GFAP by the relative area of immunostaining in ImageJ. Results. CASP3 expression in hippocampal neurons increases by 2.3 and 5.7 times on day 4 and by 1.8 and 3.9 times on day 7 of experimental SAH (groups 1–4) compared to intact group. GFAP expression increases in all observation groups compared to intact animals with the maximum values in the 5th group – by 8.14 times. The dynamics of NeuN expression in hippocampal neurons when using acelysin and nimotop corresponds to the inverse dynamics of CASP3 expression. The NeuN expression increases maximally on the 7th day of acelysin use and is equal to 91.76 % of the intact group values. Мета роботи – імуногістохімічне дослідження нейронів та астроцитів гіпокампа щурів у різні терміни експериментального крововиливу в умовах застосування ацелізину та німотопу. Матеріали та методи. Субарахноїдальний крововилив (САК) моделювали на 35 щурах лінії Вістар, яких поділили на 7 груп. Тварини 1 і 2 груп протягом 4 і 7 діб відповідно отримували ацелізин у дозі 15 мг/кг один раз на добу; тварини 3 і 4 груп упродовж 4 і 7 діб одержували німодипін у дозі 0,3 мг/кг кожні 8 годин. У 5 і 6 групах (контрольні) моделювали САК без лікування, терміни спостереження – 4 і 7 діб відповідно. Інтактні тварини сформували 7 групу. Модель САК відтворена з урахуванням методики R. V. Dudhani et al. У гістологічних зразках поля СА1 гіпокампа за допомогою програми ImageJ оцінювали відносну площу імуногістохімічної експресії CASP3 та NeuN у нейронах, GFAP в астроцитах тварин усіх груп. Результати. Експресія CASP3 у нейронах гіпокампа зростає у 2,3 та 5,7 раза на 4 добу, в 1,8 та 3,9 раза – на 7 добу експериментального САК (групи 1–4) щодо показника інтактної групи. Експресія GFAP суттєво зростає в усіх групах спостереження щодо параметрів інтактних тварин, максимальні показники зафіксовано в 5 групі – збільшення експресії в 8,14 раза. Динаміка експресії NeuN в нейронах гіпокампа при використанні ацелізину й німотопу відповідає зворотній динаміці експресії CASP3. Експресія NeuN максимально підвищується на 7 добу використання ацелізину і становить 91,76 % від показників інтактної групи.
Вплив ацелізину та німотопу на клітинну відповідь гіпокампа в динаміці експериментального субарахноїдального крововиливу
Polkovnikov O. Yu. - ORCID ID: 0000-0003-2174-9849; Tertyshnyi S. I. - ORCID ID: 0000-0003-3856-4234.
Keywords: subarachnoid hemorrhage; cerebral aneurysm rupture; GFAP; NeuN; CASP3; САК; розрив церебральної аневризми